Interaction between limulus amoebocyte lysate and soluble antigens from Pseudomonas aeruginosa and Staphylococcus aureus studied by quantitative immunoelectrophoresis. - Baek, L (1985)
To investigate the interaction of Limulus amoebocyte lysate (LAL) with gram-negative bacteria, soluble antigens from sonicated Pseudomonas aeruginosa were studied by various crossed-immunoelectrophoresis methods before and after reaction with LAL. Of 64 possible, at least 7 antigens were affected, as indicated by precipitin pattern, after the reaction with LAL. The precipitates corresponding to lipopolysaccharide and Pseudomonas "common antigen" disappeared. This reaction was inhibited when LAL was pretreated with lipopolysaccharide or by heating. Several of the reacting antigens have been shown to cross-react with many other strains of both gram-negative and gram-positive bacteria. Soluble antigens from a protein A-deficient strain of Staphylococcus aureus were also studied. LAL reacted with at least four of these antigens, including the teichoic acid complex. It is concluded that LAL is highly reactive with lipopolysaccharide, but it can react with other antigens from gram-negative and gram-positive bacteria as well. It is suggested that LAL interacts with biologically important antigens from the bacterial membrane. It is proposed that the reactivity and specificity of LAL for various microbial antigens can be studied by immunoelectrophoretic techniques.